IMPLEMENTATION OF EMPLOYEE PERFORMANCE ASSESSMENT IN POLYTECHNIC KUTARAJA - Ferdi Revita; Hasbi (JURNAL KREASI RAKYAT, 2023)
In general, in building employee performance, companies will give bonuses to each of their employees if they get good marks in carrying out their duties. The bonus can be a motivation for employees to improve their performance. Performance appraisal is carried out between superiors and subordinates and looks at the work of employees in the last year. This study aims to determine the implementation of employee performance appraisal at the Kutaraja Polytechnic. The method used in this study is a quantitative descriptive method in the form of primary data, namely research that seeks to describe and interpret existing conditions or relationships. The data sources used in this study are secondary data sources, namely data sources obtained indirectly or using media and second-party intermediaries. The results of the study revealed that employee performance indicators are tools used to measure work performance at the Kutaraja Polytechnic in accordance with their respective authorities and responsibilities and performance characteristics are the basic capital in achieving employee career success.